Ventilation-Like Mechanical Strain Modulates the Inflammatory Response of BEAS2B Epithelial Cells. (19th June 2019) - Spassov, Sashko G.; Kessler, Christoph; Jost, Rebecca; Schumann, Stefan
Abstract : Protective mechanical ventilation is aimed at preventing ventilator-induced lung injury while ensuring sufficient gas exchange. A new approach focuses on the temporal profile of the mechanical ventilation. We hypothesized that the temporal mechanical strain profile modulates inflammatory signalling. We applied cyclic strain with various temporal profiles to human bronchial epithelial cells (BEAS2B) and assessed proinflammatory response. The cells were subjected to sinusoidal, rectangular, or triangular strain profile and rectangular strain profile with prestrain set to 0, 25, 50, or 75% of the maximum stain, static strain, and strain resembling a mechanical ventilation-like profile with or without flow-controlled expiration. The BEAS2B response to mechanical load included altered mitochondrial activity, increased superoxide radical levels, NF-kappaB translocation, and release of interleukin-8. The response to strain was substantially modulated by the dynamics of the stimulation pattern. The rate of dynamic changes of the strain profile correlates with the degree of mechanical stress-induced cell response.